Muhammadiyah and Civil Society: Critical Network, Patterns of Criticism, and Challenges - Ozi Setiadi (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
Muhammadiyah is an Islamic organization that aims to form a charitable civil society and has a productive and independent network from the state. Muhammadiyah carries out a critical function in carrying out checks and balances for the state. This is done by using the criticality network. This study discusses critical networks, patterns of spreading criticism, and challenges for Muhammadiyah. This research is library research with a qualitative approach. The data collection technique used is a literature study, which is strengthened by interviews with related elements. The results of this study indicate that Muhammadiyah's critical network is divided into two, namely formal and non-formal networks. The pattern of spreading criticism is in the form of a pyramid. Nevertheless, Muhammadiyah faces challenges such as the exclusivity of thought, accommodation to “progressive” institutions affiliated with Muhammadiyah, and debates over concepts that are generally born from the womb of Western thought. This research shows that Muhammadiyah as civil society has a productive network to carry out checks and balances to the state. As a developing civil society, it still has challenges to overcome.